A new species of Hemilea Loew and two new records of Trypetini (Diptera: Tephritidae: Trypetinae) from India - David, K.j.; Hancock, D.l.; Sachin, K.; Sankararaman, H. (Zootaxa, 2020)
A new species of Hemilea Loew, H. totu David, Hancock & Sachin, sp. n., is described from India. Paratrypeta appendiculata (Hendel) and Vidalia thailandica Hancock & Drew are recorded for the first time from India and a key to species of Hemilea from India and Myanmar is provided.